Cyclin-dependent kinases as mediators of aberrant transcription in prostate cancer - Razia Rahman; Luke A. Selth (Translational Oncology)
Transcriptional control of gene expression is fundamental to all cellular processes. Conversely, transcriptional dysregulation is a hallmark of cancer. While this hallmark is a key driver of all malignancy-related process, it also represents a vulnerability that can be exploited therapeutically. Prostate cancer is a prime example of this phenomenon: it is characterised by aberrant transcription and treated with drugs that influence transcriptional pathways. Indeed, the primary oncogenic driver and therapeutic target of prostate cancer, the androgen receptor (AR), is a transcription factor. Moreover, a plethora of other transcriptional regulators, including transcriptional cyclin-dependent kinases (CDK7, CDK8 and CDK9), MYC and Bromodomain-containing protein 4 (BRD4), play prominent roles in disease progression. In this review, we focus on the roles of transcriptional CDKs in prostate cancer growth, metastasis and therapy resistance and discuss their interplay with AR, MYC and BRD4. Additionally, we explore recent advances in the therapeutic targeting of transcriptional CDKs and propose how these strategies could be effectively harnessed for the treatment of prostate cancer.